2016
DOI: 10.1016/j.tox.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the gender differences of the natural resistance to antivitamin K anticoagulants in rats

Abstract: Vitamin K antagonists (VKA) are used either in human medicine to prevent thromboembolic disorders or as rodenticides for pest control management. In rodents, female rats are described to be more tolerant to the action of vitamin K antagonists than males. Nevertheless, the mechanism of this greatest tolerance is still unknown and this study aims to identify the origin of this greatest tolerance after VKA administration. Therefore, difethialone, one of the most powerful VKA was used in this study. A possible dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
2
6
1
Order By: Relevance
“…VKA rodenticides are characterized by a wide interindividual variability of response between rats due to gender, environmental and genetic factors 1,5,6 . The origin of the gender differences in the response to VKA rodenticides has been reported in different rat strains: in Sprague-Dawley rats, a higher basal activity of FVII and FX has been found in females compared to males, in agreement with results of older studies in Wistar rats 6,7 . Besides, resistance to VKA rodenticides due to genetic factors has been reported in both genders from many countries in Europe but also in United States, Canada, Japan and Australia resulting in a serious concern for pest control [8][9][10] ].…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…VKA rodenticides are characterized by a wide interindividual variability of response between rats due to gender, environmental and genetic factors 1,5,6 . The origin of the gender differences in the response to VKA rodenticides has been reported in different rat strains: in Sprague-Dawley rats, a higher basal activity of FVII and FX has been found in females compared to males, in agreement with results of older studies in Wistar rats 6,7 . Besides, resistance to VKA rodenticides due to genetic factors has been reported in both genders from many countries in Europe but also in United States, Canada, Japan and Australia resulting in a serious concern for pest control [8][9][10] ].…”
Section: Introductionsupporting
confidence: 80%
“…Half-lives of the vitamin K dependent factors following difethialone intoxication had been previously estimated in aliquots collected during this same study 7 and reported: 2.9h for FVII, 5.5h for FX, 11h for FII and 12.6h for FIX. Based on the time to halving values, ETP and PH were ranked: in both genders, FVII decreased first, followed by FX, then ETP, PH, and FII then finally by FIX.…”
Section: Changes Of Thrombin Generation Over Time Aftermentioning
confidence: 71%
See 1 more Smart Citation
“…In our model, the limited intake of vitamin K associated with the presence of the VKORC1 mutation leads to decrease of the pool of activated vitamin K-dependent clotting factors but not sufficiently to lead to hemorrhagic syndrome. Indeed, to modify the prothrombin time in rats, it was demonstrated that reduction of at least 70% of activity of factor II was required 46 . This reduction in our model is only of 40%.…”
Section: Discussionmentioning
confidence: 99%
“…Microsomal VKOR activity was assayed as described previously, and characterisation of VKOR activity was performed by determining K m , V max and K i towards various AVKs, as described previously . The resistance factor of VKOR activity catalysed by VKORC1 spr was calculated by dividing the K i obtained for VKORC1 spr by the corresponding K i obtained for VKORC1 dom .…”
Section: Methodsmentioning
confidence: 99%